Inwestycje a konkurencyjność przedsiębiorstw innowacyjnych w Polsce - Gryko, Józefa Monika (Investments and Competitiveness of Innovative Enterprises in Poland, 2007)
The paper describes connections between competitive position of an innovative enterprise and its investment activity size and directions. Research and development activities are one of the conditions for creation and sustaining of competitive advantage for innovative enterprises. They have to make specific investment decision, dedicated to acquire adequate amount of assets, either material, which are traditionally recognized as a source of competitive advantage, or intangible assets, which are essential for competitive advantage in high technology sector. Relations between research and development investments and innovative enterprises results are illustrated by statistical data (1998-2004) on R&D activities of industrial enterprises in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 206-215